أهمية التسويق المركزي في تعزيز الثقافة الصحيّة وإدارة مخازن المطاعم. (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2016)
يسعى البحث لتعزيز دور التسويق المركزي في إضافة قيمة مضافة من المنافع التسويقية في المطاعم، والدور الذي يلعبه التخزين، بشكل عام، والبرادات وغرف التبريد، بشكل خاص، في تحقيق منافع زمانيّة للمنتجات، والتوازن بين تدفق المواد والمستلزمات اللازمة؛ لاستمراريّة العمليّة الإنتاجيّة، أجري البحث على عينة مثلت نحو 50 مطعمًا في محافظة اللاذقية، وتوصّلت النتائج إلى أنّ للتسويق المركزي دورًا مهمًّا في رفع مستوى ثقافة الخدمات التسويقيّة وصحيّتها.The research seeks to enhance the role of the central marketing to added value marketing benefits in restaurants, the role of storage in general, and refrigerators cooling rooms in particular in achieving temporal benefits of the products and the balance between the flow of materials and supplies necessary for the continuity of the production process. theresearch was conducted on a sample thate represented about 50 Restaurant in Latakia province, and reached the results thate the central marketing has an important role in raising the level of culture and health for marketing services.